2021
DOI: 10.23960/jpp.v11.i1.202109
|View full text |Cite
|
Sign up to set email alerts
|

Implementation HOTS Based-Learning during Covid-19 Pandemic in Indonesian Elementary School

Abstract: Implementation HOTS Based-Learning during Covid-19 Pandemic in Indonesian Elementary School. Objective: This research aims to describe the learning process oriented HOTs in midst of the Covid-19 pandemic outbreak. Method: This research is a qualitative research with phenomenological research type.The data was collected by phone interview to 17 elementary school teachers in Central Java Province. Data analysis is using Bogdan & Biklen models. Findings: The results showed that the application of HOTs-based learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The results at the Analysis stage revealed that the learning applied in schools was still not oriented to HOTS empowerment. This finding is in line with several other studies that report that HOTS-oriented learning has not been implemented optimally in various schools in Indonesia (Fatimahtuzzahroh et al, 2021;Ramdiah et al, 2019). The lack of implementation of HOTS-based learning in Indonesia can be caused by several causes.…”
Section: Discussionsupporting
confidence: 91%
“…The results at the Analysis stage revealed that the learning applied in schools was still not oriented to HOTS empowerment. This finding is in line with several other studies that report that HOTS-oriented learning has not been implemented optimally in various schools in Indonesia (Fatimahtuzzahroh et al, 2021;Ramdiah et al, 2019). The lack of implementation of HOTS-based learning in Indonesia can be caused by several causes.…”
Section: Discussionsupporting
confidence: 91%
“…How do the biology teachers train HOTS for students during the pandemic? Previous researchers had uncovered teachers' knowledge about HOTS, HOTS-based learning preparation, and implementation of HOTS-based learning (Fatimahtuzzahroh et al, 2021;Ichsan et al, 2020;Ritonga et al, 2021;Sa'adah et al, 2020;Sirait et al, 2021). The current research will reveal these aspects at the high school level on specific subject of Biology.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, it is also strengthened by research (Fariska & Erman, 2017) lowering student HOTS in courses microbiology caused evaluation more Emphasis on results study. This is reinforced by research (Maulia Fatimahtuzzahroh et al, 2021) Findings: The results show that the implementation of HOTs-based learning during the pandemic: 1) teacher knowledge about HOTS learning is quite good, 2) HOTS-based learning process planning is still not optimal, 3) The HOT-based learning process has not been implemented optimally. So that HOTS students increase as an alternative by implementing a hybrid learning model in learning microbiology.…”
Section: Introductionmentioning
confidence: 90%